Penerapan Metode Talqin dalam Meningkatkan Kemampuan Menghafal Al-Qur’an di Madrasah Ibtidaiyah Terpadu Tahfidzul Qur’an Al-Ma’shum Surakarta - Kinesti, Rakanita Dyah Ayu; Rohmawati, Geta; Azizy, Faza Al-; Khotimah, Khusnul (Lembaga Yasin AlSys, 2023)
Background: Memorizing the Qur'an in today's era is not only applied in Islamic boarding schools, but schools are starting to be crowded. One of them is MI Terpadu Tahfidzul Qur'an Al-Ma'shum Surakarta which aims to produce a generation of Qur'anis who have faith and charisma morals through the development of multiple intelligences in an integrated manner. Through Qur'an and thematic learning that is carried out daily, these goals can be achieved optimally. The memorization target for the kutab program is 15 juz for 6 years. The method used is the talqin method. Objective: Describe the application of the talqin method in improving the ability to memorize the Qur'an in MI Terpadu Tahfidzul Qur'an Al-Ma'shum Surakarta. Method: This research uses qualitative methods of field study type at MI Terpadu Tahfidzul Qur'an Al-Ma'shum Surakarta. Data collection techniques through observation, interviews, and documentation from madrasah educators and students. Result: The talqin method is applied by the way the ustadzah recites part of the verse and then the students follow. If the student's reading is in accordance with tajweed and correct, then the student's task is to memorize the verse and later it is deposited into the ustadzah again. One verse can be cut into several parts so that children can easily imitate the reading of the ustadzah. This method is effectively applied in improving students' ability to read and memorize the Qur'an, especially at the age of children just entering ibtidaiyah madrassas such as grade 1 kutab which I make this observation place.